Efficacy of topical hyaluronic acid for symptomatic oral lichen planus: A systematic Review - Sadeq A. Al-Maweri; Rawan Alanazi; Mohammed Nasser Alhajj; Ammar Daer; Abdulrahman Ahmed Hunaish; Abdullah Bin Nabhan; Abeer A. Al-Sosowa (Universidad de Concepción., 2021)
Department of Periodontics, School of Stomatology, Lanzhou University, Lanzhou, China. Department of Periodontics, Faculty of Dentistry, Thamar University, Dhamar, Yemen.